2000
DOI: 10.1086/303012
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Tuberculosis to Chromosome 2q35 Loci, Including NRAMP1, in a Large Aboriginal Canadian Family

Abstract: An epidemic of tuberculosis occurred in a community of Aboriginal Canadians during the period 1987-89. Genetic and epidemiologic data were collected on an extended family from this community, and the evidence for linkage to NRAMP1, a candidate gene for susceptibility to mycobacterial diseases, was assessed. Individuals were grouped into risk (liability) classes based on vaccination, age, previous disease, and tuberculin skin-test results. Under the assumption of a dominant mode of inheritance and a relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 41 publications
4
119
0
4
Order By: Relevance
“…55 Because of the critical role of Nramp1 in the mouse model of typhoid fever, the human homologue of mouse NRAMP1 was investigated in resistance to typhoid fever in humans. Despite the fact that NRAMP1 contributes clearly to the risk and the progression of mycobacterial infections in humans, 7,[64][65][66] no allelic association was identified between NRAMP1 and typhoid fever susceptibility in humans in southern Vietnam. 67 However, these studies do not preclude a role for NRAMP1 in susceptibility to human Salmonella infections because of the known effect of the ethnic genetic background on the expression of disease susceptibility.…”
Section: Nramp1mentioning
confidence: 95%
See 1 more Smart Citation
“…55 Because of the critical role of Nramp1 in the mouse model of typhoid fever, the human homologue of mouse NRAMP1 was investigated in resistance to typhoid fever in humans. Despite the fact that NRAMP1 contributes clearly to the risk and the progression of mycobacterial infections in humans, 7,[64][65][66] no allelic association was identified between NRAMP1 and typhoid fever susceptibility in humans in southern Vietnam. 67 However, these studies do not preclude a role for NRAMP1 in susceptibility to human Salmonella infections because of the known effect of the ethnic genetic background on the expression of disease susceptibility.…”
Section: Nramp1mentioning
confidence: 95%
“…6 The contribution of the host genetic background to the risk of infection and disease severity has been evidenced in humans by studies documenting racial differences in disease susceptibility, a higher concordance in monozygotic vs dizygotic twins and, more recently, using large-scale family-based genome scans and association studies. [7][8][9] It is clear from these genetic analyses that the molecular mechanisms of resistance and susceptibility to infectious diseases are extremely complex and multifactorial with microbial virulence determinants and geographical environment factors modifying the expression of specific host susceptibility loci.…”
Section: Introductionmentioning
confidence: 99%
“…The NRAMP1 gene has also been linked or associated with tuberculosis susceptibility. [10][11][12] Recently, the extent of Mitsuda reactivity was shown to be linked to NRAMP1, suggesting that NRAMP1 itself may control important aspects of anti-M. leprae immune responsiveness. 4 Finally, a genome-wide scan for leprosy susceptibility loci, conducted in mostly paucibacillary leprosy families, identified a locus on chromosome 10.…”
Section: Introductionmentioning
confidence: 99%
“…Second, several primary immunodeficiency disorders are associated with susceptibility to mycobacteria in a Mendelian fashion attributable to rare single gene mutations with high penetrance [5]. Third, several genome-wide studies of susceptibility to TB have been performed with family-based linkage studies and have identified several promising chromosomal loci [16][17][18][19]. Fourth, candidate gene association studies, which evaluate whether common polymorphisms in candidate genes are associated with susceptibility to disease, suggest several loci that are associated with Tb susceptibility.…”
Section: Disease Mechanism 1: Macrophages Genetics and The Innate Imentioning
confidence: 99%